Psychological Torture: Definition, evaluation and measurement, By Pau Pérez-Sales - Jaranson, Jim (Torture Journal, 2017)
Psychiatrist Pau Pérez-Sales has compiled a masterful and thorough analysis of an ambiguous but extremely important topic using a multidisciplinary approach. The book’s objectives are to define torture, to build a theoretical framework for understanding and re-defining torture, to propose operational criteria for research, to propose working criteria for deciding whether a case constitutes torture and, finally, to propose adjustments in the Istanbul Protocol for documentation of torture. The author has accomplished all of these objectives successfully in a book that is well-written and easy to read, even though he draws from the esoteric concepts and language of legal, political, and scientific fields.